Postharvest Pruning Guide for Hops in Florida - Mariel Gallardo; Shinsuke Agehara; Chistopher DelCastillo; Jack Rechcigl (EDIS)
In Florida, hops have two growing seasons per year, and different pruning practices are recommended after each season. This article explains why, when, and how to prune hops in Florida. It is part of a series that examines the challenges and opportunities of hop production in Florida based on research at the UF/IFAS Gulf Coast Research and Education Center. Written by Mariel Gallardo, Shinsuke Agehara, Christopher DelCastillo, and Jack Rechcigl, and published by the UF/IFAS Horticultural Sciences Department; 3 pp. https://edis.ifas.ufl.edu/hs1439